High‐risk HPV testing on self‐sampled versus clinician‐collected specimens: A review on the clinical accuracy and impact on population attendance in cervical cancer screening. Issue 10 (14th September 2012) - Snijders, Peter J.F.; Verhoef, Viola M.J.; Arbyn, Marc; Ogilvie, Gina; Minozzi, Silvia; Banzi, Rita; van Kemenade, Folkert J.; Heideman, Daniëlle A.M.; Meijer, Chris J.L.M.
Abstract: This review elaborates on the accuracy and feasibility of human papillomavirus (HPV) self‐sampling, i.e ., offering self‐sampling of (cervico‐)vaginal cell material by women themselves in nonclinical settings for high‐risk HPV (hrHPV) detection in the laboratory, for cervical screening. To that end a bibliographic database search (PubMed) was performed to identify studies (published between January 1992 and January 2012) that compared clinical accuracy of HPV testing on self‐sampled material with that of cytology or HPV testing on clinician‐taken samples, and studies comparing response to offering HPV self‐sampling with a recall invitation. Overall, hrHPV testing on self‐samples appeared to be at least as, if not more, sensitive for cervical intraepithelial neoplasia grade 2 or worse (CIN2+) as cytology on clinician‐obtained cervical samples, though often less specific. In most studies, hrHPV testing on self‐ and clinician‐sampled specimens is similarly accurate with respect to CIN2+ detection. Variations in clinical performance likely reflect the use of different combinations of collection devices and HPV tests. Because it is known that underscreened women are at increased risk of cervical cancer, targeting non‐attendees of the screening program could improve the effectiveness of cervical screening. In developed countries offering self‐sampling has shown to be superior to a recall invitation for cytology in re‐attracting original non‐attendees into the screening program. Additionally, self‐testing has shown to facilitate access to cervical screening for women in low resource areas. This updated review of the literature suggests that HPV self‐sampling could be an additional strategy that can improve screening performance compared to current cytology‐based call‐recall programs.